Respuesta :

We are told to the write the given expression in standard form ;

[tex]{:\implies \quad \sf \dfrac{6.6\times 10^{-2}}{3.3\times 10^{-4}}}[/tex]

Rewrite as ;

[tex]{:\implies \quad \sf \dfrac{66\times 10\times 10^{-2}}{33\times 10\times 10^{-4}}}[/tex]

[tex]{:\implies \quad \sf \dfrac{2\times 10^{-2}}{10^{-4}}}[/tex]

[tex]{:\implies \quad \sf 2\times \dfrac{10^{-2}}{10^{-4}}}[/tex]

[tex]{:\implies \quad \sf 2\times 10^{-2-(4)}\quad \qquad \bigg\{\because \dfrac{a^m}{a^n}=a^{m-n}\bigg\}}[/tex]

[tex]{:\implies \quad \sf 2\times 10^{-2+4}}[/tex]

[tex]{:\implies \quad \boxed{\bf{2\times 10^{2}}}}[/tex]

This is the required answer